Response of overstory and understory vegetation 37 years after prescribed burning in an aspen-dominated forest in northern Minnesota, USA – A case study. (2nd January 2018) - Dhar, A.; Baker, C. D.; Massicotte, H. B.; Palik, B.; Hawkins, C. D. B.
Abstract: Many studies have examined short-term changes in understory vegetation following prescribed burning. However, knowledge concerning longer term effects on both forest understory and overstory vegetation is lacking. This investigation was initiated to examine changes in understory (herbaceous and shrub) and overstory species composition almost four decades after logging and prescribed burning at the Pike Bay Experimental Forest in Minnesota. The experiment was established in 1964 with a randomized block design with four treatments: control (c); burned in spring 1967 (S0); burned in spring 1967 + repeat burn spring 1969 (S2); and burned in spring 1967 + repeat burn fall 1970 (F4). Overstory and understory species diversity indices and richness varied within and among treatments but were not strongly or consistently affected by the treatments. Multivariate analyses (multi-response block permutation procedures and non-metric multidimensional scaling) reveal some lingering effects of burning intensity and seasonal variation as well as some compositional differentiation among treatments, but only in the herb layer. In this environment, the effects of two repeated burnings (fire) have essentially disappeared for overstory and understory species diversity and community composition and have failed to convert an aspen-dominated stand to a coniferous stand (an original goal of the study).